GOSSIP AS A CULTURAL FORMULA AND AS THE AUDIENCES’ DESIRES IN SHONDA RHIMES’ BRIDGERTON SEASON 1 NETFLIX SERIES - Alisya Rusdianti; Naruemon Yamareng (CALL, 2026)
Gossip, in Briderton Season 1 series, is a deeply held cultural practice in society; every community engages in discovering and sharing specific information through gossip. It captures viewers’ interest, contributing to the show’s popularity. It is shown by the audience’s enthusiastic in Instagram posts through several comments. Cawelty’s formula becomes the theoretical focus of this study, which is then linked to Lacan’s concept of desire to demonstrate how the gossip formula functions as a cultural signifier and an expression of societal desire. The method applied is qualitative descriptive to elaborate the data. The data related with audiences are compiled from Instragram @bridgertonnetflix, included 10 post and 100 comments entangled to the posts. The results of this study indicate that gossip serves as a cultural formula deeply ingrained in the audience; the audience’s active anaclitic and active narcissistic desires are fulfilled by the romance and gossip elements present in the Bridgerton series.